Manajemen Media Pembelajaran Interaktif dalam Meningkatkan Prestasi Belajar Siswa (Studi Kasus Siswa SDN Bukitmulya Kabupaten Cianjur) - H. Soro, Suharyanto; Suherman, Maman; Nuraeni, Ani; Muharisa, Dini; Nurihayati, Emilya (LP. Ma'arif Janggan Magetan, 2024)
The use of learning media is one of the efforts made by teachers in order to improve student learning achievement. However, the existence of learning media has not maximized its function in the teaching and learning process. In general, the use of learning media can be synchronized through proper management so that its function is maximized. This study aims to find and describe the management of the use of interactive learning media in improving student learning achievement at SDN Bukitmulya, Cianjur Regency. The research method uses a qualitative method with a case study approach. Data were collected through observation, in-depth interviews, and documentation. Research participants consisted of principals, teachers, and students. The results of the study showed that: (1) Management of interactive learning media carried out properly and systematically can improve student learning achievement; (2) Teachers play a strategic role as facilitators and managers of learning, while adequate technological support and teacher training are the main supporting factors; (3) Students become more active, enthusiastic, and involved in the learning process, because the learning process becomes more interesting and enjoyable, teachers also feel an increase in the effectiveness of teaching with this interactive media.